Searches for baryon number violation in neutrino experiments: a white paper - Dev, P S B; Koerner, L W; Saad, S; Antusch, S; Askins, M; Babu, K S; Barrow, J L; Chakrabortty, J; de Gouvêa, A; Djurcic, Z; Girmohanta, S; Gogoladze, I; et al. (Journal of physics. G, Nuclear and particle physics, 2024)
Baryon number conservation is not guaranteed by any fundamental symmetry within the standard model, and therefore has been a subject of experimental and theoretical scrutiny for decades. So far, no evidence for baryon number violation has been observed. Large underground detectors have long been used for both neutrino detection and searches for baryon number violating processes. The next generation of large neutrino detectors will seek to improve upon the limits set by past and current experiments and will cover a range of lifetimes predicted by several Grand Unified Theories. In this White Paper, we summarize theoretical motivations and experimental aspects of searches for baryon number violation in neutrino experiments.